Ethnic Chinese in Indonesia - Winarta, Frans Hendra (LAW REVIEW, 2002)
In May 1998 riots, it was reported that 1200 people killed and more than 160 women gangraped. The victims are ethnic Chinese. The May 1998 riots are inhuman. The protection of a citizens life is a right of every citizen guaranteed under the Indonesian Constitution. Article 281 paragraph 2 of 1945 constitution states that "Everyone has the right to be free from any discriminative action on whatever basis and is entitled to a protection from such discriminative action." This provision should annul the discriminative laws and regulations. Any laws and legislations repugnant to it should be considered void. This will accelerate the integration of the ethnic Chinese. A serious, clear and conducive agenda on implementing legal reform must be continued to pull up by the roots all discriminative provisions.Â